2022
DOI: 10.3390/venereology2010001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Comorbidities and Associated Factors among HIV Patients Attending Antiretroviral Clinics in the Tamale Metropolis, Ghana

Abstract: Human Immunodeficiency Virus (HIV) is a chronic infectious disease, and without antiretroviral therapy (ART), it is associated with comorbidities. The prevalence of comorbidities, adherence to ART and quality of life (QoL) of HIV patients were studied. A cross-sectional study design involving 360 HIV patients from two ART clinics across the Tamale metropolis was employed. Socio-demography, adherence to therapy, and QoL data were taken with the help of a questionnaire and analyzed using SPSS version 24. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
2
2
0
Order By: Relevance
“…This nding is consistent with the studies conducted in Ethiopia and other countries. It is consistent with the study conducted in Southern Ethiopia (21.9% (95% CI: 18.3-25.4%) [20], South Africa (23.59% and 22.6%) [8, 10], Malawi (26.6%) [9] and Ghana (30.2%) [21]. The similarity in ndings might be attributed to similar methodologies using cross-sectional design, similar diagnostic methods, similar HIV treatment protocols or ART programs, or the widespread impact of HIV and NCDs.…”
Section: Discussionsupporting
confidence: 92%
“…This nding is consistent with the studies conducted in Ethiopia and other countries. It is consistent with the study conducted in Southern Ethiopia (21.9% (95% CI: 18.3-25.4%) [20], South Africa (23.59% and 22.6%) [8, 10], Malawi (26.6%) [9] and Ghana (30.2%) [21]. The similarity in ndings might be attributed to similar methodologies using cross-sectional design, similar diagnostic methods, similar HIV treatment protocols or ART programs, or the widespread impact of HIV and NCDs.…”
Section: Discussionsupporting
confidence: 92%
“…Across the globe, different co-morbidities are prevalent among HIV patients. Tuberculosis, diabetes as co-morbid conditions have been prominent diseases among HIV patients in different countries [39][40][41][42]. In our study, hypertension, diabetes, tuberculosis, and Hepatitis B were found to be signi cant co-morbidities.…”
Section: Discussionsupporting
confidence: 45%
“…HIV-1 is the causative agent for AIDS, which makes them highly susceptible to fatal and opportunistic infections and other diseases, including opportunistic infections such as tuberculosis (TB), hypertension, hepatitis, lipidemia, diabetes, asthma, and mental health issues [ 72 , 73 , 74 , 75 ]. The accompanied diseases make HIV treatment complex and warrant drug interaction studies (drug–drug, drug-food, and drug-disease interaction) [ 69 ].…”
Section: Discussionmentioning
confidence: 99%